2018
DOI: 10.3390/brainsci8080138
|View full text |Cite
|
Sign up to set email alerts
|

Spinal Cord Stimulation for Neuropathic Pain: Current Trends and Future Applications

Abstract: The origin and the neural pathways involved in chronic neuropathic pain are still not extensively understood. For this reason, despite the wide variety of pain medications available on the market, neuropathic pain is challenging to treat. The present therapeutic alternative considered as the gold standard for many kinds of chronic neuropathic pain is epidural spinal cord stimulation (SCS). Despite its proved efficacy, the favourable cost-effectiveness when compared to the long-term use of poorly effective drug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
60
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(61 citation statements)
references
References 54 publications
0
60
0
1
Order By: Relevance
“…In recent years, the Federal Food and Drug Administration (FDA) has approved market applications for a myriad of new indications for bioelectronic medicines including diverse conditions such as obesity, sleep apnea, migraine, opioid withdrawal symptoms, dry eye, essential tremor, and hypertension. These supplement traditional market indications for bioelectronic medicines such as pain and overactive bladder . Additional areas of research currently beginning early stage clinical testing include the use of therapeutic electrical stimulation to treat inflammation, metabolism, and endocrine disorders .…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the Federal Food and Drug Administration (FDA) has approved market applications for a myriad of new indications for bioelectronic medicines including diverse conditions such as obesity, sleep apnea, migraine, opioid withdrawal symptoms, dry eye, essential tremor, and hypertension. These supplement traditional market indications for bioelectronic medicines such as pain and overactive bladder . Additional areas of research currently beginning early stage clinical testing include the use of therapeutic electrical stimulation to treat inflammation, metabolism, and endocrine disorders .…”
Section: Introductionmentioning
confidence: 99%
“…Related to gastric digestion, bowel and bladder function, 8 of 13 patients improved after SCS implantation (p < 0.05) ( Table 5), and finally, related to adverse effects, one of the patients had electrode migration, in the second patient, there was infection at the site of the generator, and the third patient had to change the percutaneous technique by open surgery, due to obesity. [7,8], as in our study population. Interesting, the population was constituted by mainly white people.…”
Section: Resultsmentioning
confidence: 96%
“…Generally used for the treatment of chronic pain since 1967 (Shealy et al, 1967 ; Dones and Levi, 2018 ), SCS consists of the application of electrical pulses in the dorsal columns of the spinal cord (directly in the epidural space). It has been suggested that the mechanism of action is based on the antidromic activation of the dorsal column fibers, which activate the inhibitory interneurons within the dorsal horn (Yampolsky et al, 2012 ).…”
Section: Electrical Neuromodulation Therapies For Pd and Hdmentioning
confidence: 99%